2016
DOI: 10.1007/s13337-016-0324-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of genotype XIII Newcastle disease virus from Emu in India

Abstract: Newcastle disease virus (NDV) infects at least 241 species of pet and free-living birds in addition to domesticated avian species. Wild, feral and domesticated birds are recognized reservoirs of NDV, and contribute to the epidemiology of NDV in the domesticated poultry. The biological and molecular characterization of velogenic NDV (vNDV) from emus is limited. In this study, 54 tissues were collected from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…In this study, we obtained AAvV-1 isolate (Emu/5, Genbank: MT178234) from an apparently healthy emu flock. Previous reports confirmed isolation of vNDV from an infected emu Molecular Characterization of Velogenic Avian Avulavirus Type 1 Isolated from Apparently Healthy Emu Birds... flock raised in a poultry dense area (Gowthaman et al, 2016). Shinde et al (2012) was 1:128 thus confirming the isolate as AAvV-1.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…In this study, we obtained AAvV-1 isolate (Emu/5, Genbank: MT178234) from an apparently healthy emu flock. Previous reports confirmed isolation of vNDV from an infected emu Molecular Characterization of Velogenic Avian Avulavirus Type 1 Isolated from Apparently Healthy Emu Birds... flock raised in a poultry dense area (Gowthaman et al, 2016). Shinde et al (2012) was 1:128 thus confirming the isolate as AAvV-1.…”
Section: Resultssupporting
confidence: 61%
“…In addition, Mean death time score in 9-11 day old embryonated chicken eggs was 48 h and ICPI score in dayold chicks was 1.82, suggesting that the isolate was highly During 2002-2003, Kinde et al (2005 reported isolation of exotic newcastle disease (END) virus from emus. Similarly, Gowthaman et al (2016) reported isolation of velogenic AAvV-1 of subgenotype XIII 2.2 from an infected emu flock with a similar motif at FPCS. ND outbreaks in commercial chicken flocks caused by subgenotype XIII 2.2 viruses were also reported in different parts of India (Jhakesara et al, 2016;Gowthaman et al, 2018).…”
Section: Resultsmentioning
confidence: 78%
“…Apart from various genotypes reported, pathotypic and sequence characterization of NDV from vaccinated chickens revealed circulation of genotype II, IV and XIII in the country [19]. Genotype XIII (XIIIb) was isolated in commercial vaccinated layer farms [20] and from Emu [21]. In the present study, partial sequencing of fusion protein gene followed by phylogenetic analysis revealed the present isolate (ADS01) that was of class II genotype NDV XIII and the finding was subsequently supported by deduced amino acid sequence analysis of F protein cleavage site which revealed a virulent amino acid motif.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiological connection between the isolates in America and those in China is however still not clear, since migratory birds have not so far been incriminated in carrying these viruses [31, 44, 45]. Genotype XIII isolates which have been recovered from birds in Europe, Asia, and Africa are all predicted to be virulent based on the amino acid composition of their F cleavage site [78]. They are thought to be continuously evolving especially in Asia and the Middle East.…”
Section: Taxonomy and Global Distribution Of Newcastle Disease Virmentioning
confidence: 99%